Formation of NixCo3−xS4 hollow nanoprisms with enhanced pseudocapacitive properties - Yu, Le (2014)
Hollow nanostructures are of great interest for a wide variety of applications. Despite the great advances, synthesis of anisotropic hollow structures is still very challenging. In this work, we have developed a simple sacrificial template method to synthesize uniform NixCo3−xS4 hollow nanoprisms with tunable composition. Tetragonal nanoprisms of nickel–cobalt acetate hydroxide precursors with controllable Ni/Co molar ratios are first synthesized and used as the sacrificial templates. After a sulfidation process with thioacetamide (TAA) in ethanol, the solid precursor prisms can be transformed into the corresponding NixCo3−xS4 hollow nanoprisms with a well-defined hollow interior. The intriguing structural and compositional features are beneficial for electrochemical applications. Impressively, the resultant NixCo3−xS4 hollow prisms manifest a high specific capacitance with enhanced cycling stability, making them potential electrode materials for supercapacitors.